Sounds in alternative scenic spaces – management experiences of Espaço PÉ DiReitO (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
Based on the dialogue between the sonorities of the scene and the management experiences of Espaço PÉ DiReitO, located on the outskirts of the country’s capital, this article aims to present possibilities for creative resolutions in order to enable and enhance sound aspects of performance works in circulation. To this end, acoustic aspects and riders of space and works are discussed, as well as a list of professionals involved in the sounds of the scene, as well as challenges and multi-perspective assignments related to the managers of alternative scenic spaces demanded by the reality of recurrent scarcity.
Keywords: Theater; Sounds; Alternative scenic space; Cultural management